Persistent idiopathic facial pain – a prospective systematic study of clinical characteristics and neuroanatomical findings at 3.0 Tesla MRI. (November 2017) - Maarbjerg, Stine; Wolfram, Frauke; Heinskou, Tone Bruvik; Rochat, Per; Gozalov, Aydin; Brennum, Jannick; Olesen, Jes; Bendtsen, Lars
Introduction: Persistent idiopathic facial pain (PIFP) is a poorly understood chronic orofacial pain disorder and a differential diagnosis to trigeminal neuralgia. To address the lack of systematic studies in PIFP we here report clinical characteristics and neuroimaging findings in PIFP. Methods: Data collection was prospective and standardized in consecutive PIFP patients. All patients underwent 3.0 MRI. Results: In a cohort of 53 PIFP patients, the average age of onset was 44.1 years. PIFP was found in more women 40 (75%) than men 13 (25%), p  < 0.001. There was a high prevalence of bilateral pain 7 (13%), hypoesthesia 23 (48%), depression 16 (30%) and other chronic pain conditions 17 (32%) and a low prevalence of stabbing pain 21 (40%), touch-evoked pain 14 (26%) and remission periods 10 (19%). The odds ratio between neurovascular contact and the painful side was 1.4 (95% Cl 0.4–4.4, p  = 0.565) and the odds ratio between neurovascular contact with displacement of the trigeminal nerve and the painful side was 0.2 (95% Cl 0.0–2.1, p  = 0.195). Conclusion: PIFP is separated from trigeminal neuralgia both with respect to the clinical characteristics and neuroimaging findings, as NVC was not associated to PIFP.